Alternatively spliced tissue factor contributes to tumor spread and activation of coagulation in pancreatic ductal adenocarcinoma. Issue 1 (27th July 2013) - Unruh, Dusten; Turner, Kevin; Srinivasan, Ramprasad; Kocatürk, Begüm; Qi, Xiaoyang; Chu, Zhengtao; Aronow, Bruce J.; Plas, David R.; Gallo, Catherine A.; Kalthoff, Holger; Kirchhofer, Daniel; Ruf, Wolfram; et al.
<x xml:space="preserve">Abstract</x> Alternatively spliced tissue factor (asTF) promotes neovascularization and monocyte recruitment via integrin ligation. While asTF mRNA has been detected in some pancreatic ductal adenocarcinoma (PDAC) cell lines and increased asTF expression can promote PDAC growth in a subcutaneous model, the expression of asTF protein in bona fide PDAC lesions and/or its role in metastatic spread are yet to be ascertained. We here report that asTF protein is abundant in lesional and stromal compartments of the five studied types of carcinoma including PDAC. Analysis of 29 specimens of PDAC revealed detectable asTF in >90% of the lesions with a range of staining intensities. asTF levels in PDAC lesions positively correlated with the degree of monocyte infiltration. In an orthotopic model, asTF‐overexpressing high‐grade PDAC cell line Pt45P1/asTF+ produced metastases to distal lymph nodes, which stained positive for asTF. PDAC cells stimulated with and/or overexpressing asTF exhibited upregulation of genes implicated in PDAC progression and metastatic spread. Pt45P1/asTF+ cells displayed higher coagulant activity compared to Pt45P1 cells; the same effect was observed for cell‐derived microparticles (MPs). Our findings demonstrate that asTF is expressed in PDAC and lymph node metastases and potentiates PDAC spread in vivo. asTF elicits global changes in gene expression likely involved in tumor progression and metastatic dissemination, and it also enhances the procoagulant potential of PDAC cells and cell‐derived MPs. Thus, asTF may comprise a novel therapeutic target to treat PDAC and, possibly, its thrombotic complications.